Topoi/graphein : mapping the middle in spatial thought - Abrahamsson, Christian (Cultural geographies + rewriting the Earth., 2018)
"In Topoi/Graphein Christian Abrahamsson maps the paradoxical limit of the in-between to revealthat to be human is to know how tolive with the difference between the known and the unknown. Using filmic case studies, including CodeInconnu, Lord of the Flies, and Apocalypse Now,and focusing on key concerns developed in the works of the philosophers Deleuze, Olsson, and Wittgenstein, Abrahamsson starts within the notion of fixed spatiality, in whichhuman thought and action are anchored in the given of identity. He then movesthrough a social world in which spatiotemporal transformations are neitherfixed nor taken for granted. Finally he edges into the pure temporality that liesbeyond the maps of fixed points and social relations. Each chapter is organized into two subjects: topoi, orexcerpts from the films, and graphein, the author's interpretation ofpresented theoriesto mirror the displacements,transpositions, juxtapositions, fluctuations, and transformations between delimited categories. A landmark work in the study of human geography, Abrahamsson's book proposes that academic and intellectual attention should focus on the spatialization between meaning and its materialization in everyday life."--